Sixties British cinema reconsidered - Petrie, Duncan J., 1963-; Williams, Melanie, 1974-; Mayne, Laura (Edinburgh University Press, 2020)
"Challenging assumptions around Sixties stardom, the book focuses on creative collaboration and the contribution of production personnel beyond the director, and discusses how cultural change is reflected in both film style and cinematic themes."--Publisher description